Quantifying the possible financial consequences of failure for making a risk based decision - Hussain, Omar; Chang, Elizabeth; Hussain, Farookh; Dillon, Tharam S. (IEEE, 2007)
In a financial e-commerce interaction it is rational for the initiating agent to analyze beforehand the possible risk in interacting with any other agent. Doing so would give the initiating agent an idea of direction in which its interaction might head and also help it to make an informed decision of its future course of action with that particular agent. For risk analysis in the context of e-commerce interactions, the initiating agent has to determine beforehand the probability of failure and the possible consequences of failure in interacting with an agent. In this paper, we propose a methodology by which the initiating agent can determine beforehand the possible consequences of failure in its resources, according to the demand of its future interaction with an agent.